Value-Added Tax on Farms – Case Study (Research Bulletins of the Faculty of Economic Sciences, 2018)
The aim of the study was to present the benefits of the transition of a farm to the general VAT rules in 2016-2017, when carrying out significant investments. The work lists individual cost groups and presents their percentage share in total costs. The analysis shows that in 2016 the audited entity obtained a tax refund in the amount exceeding PLN 200 000 PLN, while in 2017 this return exceeded PLN 150 000. The farm, when settling on a lump sum in 2016, would have to incur additional costs related to paying VAT on purchased goods and services. The high value of VAT refund in the analyzed period was related to the investment in the modernization of a farm with a value exceeding 1.115 million gross PLN.
Keywords: VAT tax, general tax, lump sum, agricultural holding, investments